Expression of neurodegenerative disease‐related proteins and caspase‐3 in glioneuronal tumours. (February 2015) - Prabowo, A. S.; Iyer, A. M.; Veersema, T. J.; Anink, J. J.; Schouten‐van Meeteren, A. Y. N.; Spliet, W. G. M.; van Rijen, P. C.; Ferrier, C. H.; Thom, M.; Aronica, E.
Abstract : Aims: Recent evidence supports the activation of mechanisms underlying cellular ageing and neurodegeneration in developmental lesions associated with epilepsy. The present study examined the ongoing cell injury and vulnerability to neuronal degeneration in glioneuronal tumours (GNT). Methods: We evaluated a series of GNT ( n  = 31 gangliogliomas, GG and n  = 30 dysembryoplastic neuroepithelial tumours, DNT). Sections were processed for immunohistochemistry using markers for the evaluation of caspase‐3 and neurodegeneration‐related proteins/pathways and their expression was correlated with the tumour features and the clinical history of epilepsy. Results: Both GG and DNT specimens contained caspase‐3‐positive cells. In GG, expression of activated caspase‐3 was negatively correlated the with the BRAF V600E mutation status. We also observed an abnormal expression of death receptor‐6 and β‐amyloid precursor protein (APP). Moreover, dysplastic neurones expressed p62, phosphorylated (p)TDP43 and pTau. Double labelling experiments showed colocalization of phosphorylated S6 (marker of mammalian target of rapamycin, mTOR, pathway activation) with pTau and p62. In GG, neuronal p62 expression was positively correlated with pS6. The immunoreactivity score (IRS) of caspase‐3, APP, DR6, p62 and pTDP43 were found to be significantly higher in GG than in DNT. Expression of APP, DR6, pTau (in GG and DNT) and caspase‐3 (in GG) positively correlated with duration of epilepsy. In GG, the expression of neuronal caspase‐3, DR6 and glial p62 was associated with a worse postoperative seizure outcome. Conclusions: Our observations in GNT provide evidence of premature activation of mechanisms of neurodegeneration which are associated with the clinical course of epilepsy in patient with GG.